Almanac of Fall - Tarr, Béla; Gulyás, Buda; Kardos, Sandor; Pap, Ferenc; Temessy, Hédi; Bodnár, Erika; Székely, Miklós B. (Facets Video, 2006)
Set exclusively in an older woman's apartment, "Almanac of Fall" follows the actions of a group of conniving characters who are motivated by money and sex. The woman's son, her nurse, and several others vie for her money as they quarrel, maneuver, and betray, creating a bitter emotional climate worthy of Strindberg. Master director Bela Tarr, in one of his few films in color, uses inventive camera angles, a constantly moving camera, and a rigid color scheme as a strategy to comment on the characters' power struggle. Often overlooked by Tarr enthusiasts, "Almanac of Fall" is an important work by this gifted and original filmmaker which marks a turning point between the social realism of his early career and the distinctive visual style of his later acclaimed films such as "Damnation", "Satantango" and "Werckmeister Harmonies". [Cover]
Keywords: DVD-Video